3D luminescent waveguides micromachining by femtosecond laser inscription in niobium germanate glass - Marcondes, Lia Mara [UNESP]; Orives, Juliane Resges [UNESP]; Nolasco, Lucas Konaka; Santos, Sabrina N.C.; Mendonça, Cleber Renato; Cardinal, Thierry; Petit, Yannick; Canioni, Lionel; Dussauze, Marc; Nalin, Marcelo [UNESP] (Elsevier, 2025)
Three-dimensional (3D) microstructures were written by femtosecond (fs) laser aiming to manufacture waveguides inside niobium germanate glasses. The laser-induced damage threshold using 1030 nm fs-laser irradiation was investigated, and the waveguides were written in different fluences. The morphology, structural information and refractive index changes of microstructures were discussed. The waveguide cross-section microscopy data shows an elliptical shape with a diameter varying with the applied pulse energy. The micro-Raman maps demonstrate the occurrence of structural modifications with different microregions along the laser propagation direction. The refractive index profiles point to the formation of at least one microregion containing a positive refractive index change along the laser propagation. Guided light transmission measurements demonstrate the formation of single-mode waveguides inscribed at low pulse energy (up to 132 nJ) and an emitting waveguide in the rare-earth-doped sample. The visible luminescent response of erbium ions in the waveguide output was demonstrated and supports the possibility of using these core waveguides for future 3D multi-functional photonic devices operating in the visible region.
Keywords: Fs-laser inscription; Glasses; Micro-optic devices; Waveguides